Medication Use in Schools - Phan, Hanna (J Pediatr Pharmacol Ther, 2020)
This article serves as a Position Statement of the Pediatric Pharmacy Association (PPA), which supports safe and effective medication use in schools. PPA recommends that schools develop comprehensive medication use policies to support safe and appropriate administration of both chronic and emergency medication in schools. These policies must address issues specific to pediatric patients, including off-label and over-the-counter medication use, various pediatric dosage forms, as well as appropriate medication storage, administration, and disposal practices. PPA also advocates for continued staff development and education regarding laws, regulations, and policies surrounding medication use in school to ensure safe and effective care of children and adolescents in the school setting.